(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The impact of cooperative learning on English classes for university students in the development of reading skills. The study was performed on 62 students enrolled in the Sciences College of the University of Masin during the 2022-2023 academic year. The study employed an experimental group of 29 students and a control group of 31 students. To examine the impact of cooperative learning in English lessons on the improvement of students’ reading skills, data were analysed using statistical software, employing Mann-Whitney U and Wilcoxon Signed-Rank tests. The outcomes of the current study indicate no significant differences between the experimental group and the control group for pre-test scores in reading skill development, self-control, avoidance, and overall averages (p>0.05). Significant differences exist between the pre-test and post-test scores of the control group across all aspects and total scores, favouring the post-test (p<0.05). There are notable disparities between the pre-test and post-test scores of the experimental group across all dimensions and total scores, favouring the post-test (p<0.05). There are notable disparities between the post-test results of the experiment and control groups across all sub-dimensions and overall scores (p<0.05). The results demonstrated that the reading proficiency advancement of the experimental group, which participated in cooperative learning, significantly exceeded that of the control group, which employed conventional methods, revealing a marked disparity between the two groups.